Optimal pulsewidth modulation (PWM) online control of a modular structured multilevel inverter (MSMI) - Ahmad Azli, N. (2001)
An inverter topology for high power applications that seems to be gaining interest lately is the modular structured multilevel inverter. (MSMI). The switching frequency constraint in a MSMI with high isolated DC voltages calls for a low switching frequency modulator such as the optimal PWM switching strategies. This paper presents a different approach in controlling a MSMI output voltage based on the optimal PWM switching strategies. For better output voltage magnitude control resolution, a curve fitting technique (CFT) for online computation of the optimal PWM switching angles is proposed. Focus is given on the CFT and the multilevel design aspect of the proposed control strategy for the MSMI. Simulation and experimental results of the MSMI operation are given to verify its performance.